Simultaneous Determination of Sulphamethoxazole and Trimethoprim in Binary Mixtures and in Tablet Using Derivative Spectrophotometry - Al-Saidi, Khaleda H; Yonis, Marwa S (Al-Nahrain Journal of Science, 2018)
Derivative spectrophotometric (first, second, third and fourth derivative) were developed for the determination of Sulphamethoxazole)SMX) and trimethoprim (TMP)antibiotic binary mixture by applying zero-crossing technique for pure synthetic mixture while simultaneous determination of (SMX) and (TMP) in tabletsusing D4at waveleanth 257.8 nm and 251.5 nm for (SMX) and (TMP) the correlation coefficient of calibration curves were 0.9992 and 0.9995. Linearity is maintained within a wide concentration range from 2.00 to 25.00 mg/l, with relative error (-0.11 and 0.60) the LOD (0.360 and 0.382 mg/L) and LOQ and (1.200 and1.275 mg/L) respectively.No interference found between both determined and those of matrices. A good accuracy and precision of simultaneous determination of (SMX), and (TMP) were confirmed by statistical analysis.The percentage recovery of the individual drugs under the established conditions is ranged from 97.23% to 102.13 %. This method was compared with the British pharmacopoeiamethodusing F test. The procedures do not require any separation step.